Propagation and utilization of grafted tomatoes in the Great Plains - Masterson, Sarah A. (Kansas State University, 2013)
Grafting with inter-specific hybrid rootstock is effective for tomato (Solanum lycopersicum) growers looking to reduce soilborne disease organically and increase fruit yield in the Southeastern US. However, production with grafted tomatoes has not been tested in the Great Plains region of the US. Small-acreage growers would like to produce grafted plants themselves, but many have difficulty with propagation due to water stress in the scion post-grafting and/or high temperatures within healing chambers. Growers may be able to reduce water stress post-grafting by removing the upper portion of the shoot to reduce leaf surface area, but no data exist on the potential effects of this practice on mature plant yield. Five high tunnel and one open-field study were conducted in 2011 and 2012 to investigate yield effects related to the use of two rootstocks and shoot removal during the grafting procedure. Grafting significantly increased fruit yield in five of the six trials (P<0.05). The average yield increases by Maxifort and ‘Trooper Lite’ rootstocks were 53% and 51%, respectively, across all trials. In some trials shoot removal during the grafting process reduced yield and could depend upon rootstock vigor. Another series of experiments were performed testing the efficacy of shoot removal for graft survival during the healing period prior to field planting. Five healing chambers designs were evaluated, and no significant effects of treatment design were observed upon grafted seedling survival. Plants grafted with no chamber had success rates of 81% to 91%. Additionally, three grafting leaf removal techniques were studied, and a partial leaf removal method had significantly higher success rates as compared to fully foliated and defoliated plants (P<0.05). Partial leaf removal may be recommended as a way to reduce water stress in the plant, and could potentially be a way to simplify the grafting process for small-scale producers.
Keywords: Solanum lycopersicum; Yield; High tunnels; Grafting; Healing chamber; Agriculture, General (0473); Horticulture (0471)